New Records of Pathogenic Bacteria from Urban Rivers in Argentina - David Kuczynski (Journal of Tropical Life Science, 2016)
Aquatic environments associated with human settlements are mostly deteriorated by untreated or poorly treated discharges. Buenos Aires city and surroundings constitutes one of the largest urbanizations of the world. High levels of pollution have been detected for its related watercourses, showing the occurrence of a diversity of pathogenic bacteria in surface waters as well in biological members of the ecosystem. In the present paper the finding of new records for the area is reported and discussed. Yersinia enterocolitica and two subspecies of Klebsiella pneumoniae were isolated from the Reconquista River, while Citrobacter freundii, Pseudomonas aeruginosa, Pseudomonas luteola, Vibrio fluvialis, and Aeromonas hydrophila were detected in the nearby Matanza and LujÃ¡nrivers.